2021
DOI: 10.3390/educsci11050218
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Implementation of Cooperative Learning in Indonesia: A Multiple Case Study

Abstract: The current study, a part of a bigger study, explored how teachers in Indonesia implemented cooperative learning (CL) in their distinct contexts. This multiple case study design used a qualitative interpretative approach. Following semi-structured interviews with 18 teachers who had attended CL professional development and used CL in their classrooms, four were purposefully selected as cases of teachers. Classroom observations, post classroom observation interviews, and field notes were employed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…In order to conduct the qualitative research, we collected the data using semi-structured interviews. This use of semi-structured interviews is in line with researchers who argue that those interviews can serve the investigation of teachers' education and teachers' practices [30,31].…”
Section: Methodssupporting
confidence: 56%
“…In order to conduct the qualitative research, we collected the data using semi-structured interviews. This use of semi-structured interviews is in line with researchers who argue that those interviews can serve the investigation of teachers' education and teachers' practices [30,31].…”
Section: Methodssupporting
confidence: 56%
“…In research centered around teachers, the primary focus lies on assessing teachers’ pedagogical competence and the utilization of instructional methods. Through a study of multiple cases, it has been observed that the implementation of CL in diverse cultural settings can result in disparate effects, posing a challenge for educators in terms of instructional strategies ( Karmina et al, 2021 ). Hence, to better facilitate the training of PE teachers in implementing CL within intricate settings, it is imperative to address challenges that may emerge during the process.…”
Section: Discussionmentioning
confidence: 99%
“…It explores the cooperative learning and implementation context. This includes environment learning as a classroom setting of teaching, (Karmina, et al, 2021). In addition, it shows that inquiry and collaborative learning engages the involvement of students as a center of learning and understanding assessment, and explores students' involvement in the lesson to build an understanding of the topic of the lesson inquiry which means collaborative learning has an impact on thinking and critical skills of students in different learning, especially on purposive communication, (Warsah, et al, 2021, pp.…”
Section: Discussionmentioning
confidence: 99%